2017
DOI: 10.1111/ijsw.12293
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital always raise life satisfaction? A comparison of South Korea and Taiwan

Abstract: This study examined the relationship between social capital and life satisfaction in an Asian context, focusing on South Korea and Taiwan. We considered two components of social capital – networks and trust – and argue that the ability of social capital to increase life satisfaction depends on the context. Using the national Life and Society survey data from South Korea (N = 978) and Taiwan (N = 1,200), our analysis found that, when several control variables, such as subjective social status, self‐reported hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Woo (2017) in a study in South Korea and Taiwan showed that social capital was positively correlated with LS in the Taiwanese sample by controlling variables such as subjective social status, self-rated health, gender, and individualism tendency while there was no significant relationship between SC and LS in the South Korean sample. The South Korean case revealed that social capital is not a good predictor for LS in an environment where success is over-emphasized [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Woo (2017) in a study in South Korea and Taiwan showed that social capital was positively correlated with LS in the Taiwanese sample by controlling variables such as subjective social status, self-rated health, gender, and individualism tendency while there was no significant relationship between SC and LS in the South Korean sample. The South Korean case revealed that social capital is not a good predictor for LS in an environment where success is over-emphasized [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of celebrity system and penetration of celebrity culture coincide with Korea’s rapid economic growth and industrialization. With the weakening of traditional values and informal social networks, Korea has become a hyper-competitive materialistic society (Huang and Ho, 2016) where individual accomplishments are highly valued and closely related to life satisfaction (Woo and Kim, 2018). Given its current social and cultural characteristics, we speculate that Korea is an ideal testing ground for the claims this study put forward, but caution is needed regarding generalization of these findings to other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [ 22 , 31 , 32 ], life satisfaction was measured by a single question: “In general, how satisfied are you with your present life?”, answered on a 5-point Likert scale ranging from 1 (very dissatisfied) to 5 (very satisfied). We drew lessons from the previous research on the classification of life satisfaction [ 24 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there have been increasing studies on how social capital affects life satisfaction [ 21 , 22 ]. The existing studies have provided evidence of the relationship between social capital and life satisfaction at the individual and aggregate levels.…”
Section: Introductionmentioning
confidence: 99%